THE PSYCHOLOGICAL STRUGGLE OF THE MAIN CHARACTER IN ERNEST HEMINGWAY’S “THE OLD MAN AND THE SEA” - Berdiyev Oston Maxmud o‘g‘li (TADQIQOTLAR, 2025)
Annotation. This article provides a comprehensive analysis of the psychological struggle of Santiago, the main character in Ernest Hemingway’s novella “The Old Man and the Sea”. Using a qualitative and descriptive methodology, the study examines Santiago’s emotional strength, inner dialogue, symbolic battle with the marlin, and the philosophical  message  of  perseverance.  The  findings  demonstrate  that  Hemingway constructs Santiago as a universal image of human dignity, moral courage, and spiritual endurance,  proving  that  victory  is  not  measured  by  material  gain  but  by  inner resilience.